The ‘permanentification’ of a regime of crisis: reinforced and enduring bordering and normalization of right-wing narratives - Clerc, Sélim; Teigelkötter, Gesa; Dahinden, Janine (My University, 2025)
In public and political discourses, 2015 was constructed as the peak of a ‘refugee crisis.’ While a crisis is supposed to be temporary by definition, it seems that many references to migration have since been associated with the label ‘crisis.’ We argue that a ‘permanentification’ of a regime of crisis has been taking place over the last years. We use the term ‘permanentification’ in the sense of a process by which a state of exception is normalized and enduring. This can be observed in two key dimensions, each with significant consequences: on the one hand, exceptional measures have become routinized, institutionalized, and normalized; on the other hand, right-wing narratives have been mainstreamed to an unprecedented degree. Taken together, these dynamics reinforce existing necropolitics, institutionalize violence, and deepen exclusion.
Keywords: asylum; border control; migration crisis; right-wing narratives